(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To map the opportunities for entrepreneurship in nursing within the field of skin wound care in the Brazilian context. Method: Scope review based on the guiding question: “What are the opportunities for entrepreneurship in nursing within the context of skin injury care in Brazil?” The review included articles, resolutions, editorials, book chapters, monographs, dissertations, and theses, all available in full text, published since 2015. The search was conducted on platforms such as SciELO, Nursing Database (BDENF), Latin American and Caribbean Health Sciences Literature (LILACS), Spanish Bibliographic Index of Health Sciences (IBECS), the Portal of Resolutions, opinions from the Federal and Regional Nursing Councils, as well as Google Scholar. Results: The final sample consisted of 28 documents and scientific articles. Among the possibilities for entrepreneurial activities in nursing, the use of laser therapy (n=14) in skin wound care, autonomous and/or freelance nursing services—primarily in home care—and the opening of private practices were highlighted. Conclusion: The study identified that nursing offers several opportunities for entrepreneurship in the care of individuals with skin wounds, particularly through the use of adjunct technologies to support healing, home care services, and private practices. These opportunities provide greater professional and social visibility and recognition.